The Influence of Creativity, Social Media, and E-Commerce on the Business Success of Mahkota Ayam in Payakumbuh - Kinanti, Verona; Alfikri; Candra, Delni Alek (Jurnal Ilmiah Ekonomi Global Masa Kini, 2025)
This study aims to analyze the influence of creativity, social media, and e-commerce on the success of the Mahkota Ayam business in Payakumbuh. Using a quantitative method with a survey approach, it involves Mahkota Ayam customer respondents. Data collected were analyzed using multiple linear regression to test each variable’s influence on business success. The results show that creativity has a positive and significant effect on Mahkota Ayam's success, as seen in increased product and service innovation that boosts customer satisfaction and loyalty. Although Mahkota Ayam uses social media as a promotional tool, this variable does not significantly affect success due to inconsistent content, low interaction, and lack of an effective digital communication strategy. Meanwhile, the e-commerce variable, especially via GoFood, has a positive and significant impact by enhancing accessibility, service speed, and convenience leading to customer satisfaction. Simultaneously, creativity, social media, and e-commerce contribute significantly to business success, with creativity and e-commerce as dominant factors. Based on these findings, Mahkota Ayam should strengthen social media management through consistent, attractive content strategies. It is also expected to keep innovating in products and services to maintain business uniqueness and optimize e-commerce use as the main transaction and market expansion channel, ensuring sustainability in increasingly competitive digital markets. Keywords: E-Commerce, Business Success, Creativity, Mahkota Ayam, Social Media